Impact of Coconut Husks on the Productivity of Conventional Solar Still: A Heat Transfer Study - Pankaj Dumka; Rishabh Rathor; Saksham Sharma; Kirti Katiyar; Harshit Gautam; Chinmay Gunawat; Dhananjay R. Mishra (Current Advances in Geography, Environment and Earth Sciences Vol. 4, 2022)
In this research article, an attempt has been made to experimentally and theoretically examine the impact of coconut husk (also called cocopeat) on the overall performance of conventional solar still (CSS). To analyze the performance of still theoretically, the heat transfer model proposed by Dunkle has been used. Pertinent parameters evaluated are partial pressure, internal heat transfer coefficients, yield, internal efficiency, and exergy efficiency. In the presence of coconut husk, there has been an increase of 94.19% in the average partial pressure of the distiller unit. For 13 h experimentation, the modified still has shown a rise of 9.63% and 2.53% in the value of and compared to CSS, respectively. Furthermore, due to the presence of coconut husk, there has been an increase of 30.89% in the distillate to high capillary action compared to CSS. Moreover, the exergy efficiency of solar still augmented with coconut husk has improved by 28.14% compared to CSS.